Action research and health system strengthening: the case of the health sector support programme in Mauritania, West Africa - Kirsten Accoe; Bruno Marchal; Yahya Gnokane; Dieng Abdellahi; Paul Bossyns; Bart Criel (BMC, 2020)
Abstract Background Access to qualitative and equitable healthcare is a major challenge in Mauritania. In order to support the country's efforts, a health sector strengthening programme was set up with participatory action research at its core. Reinforcing a health system requires a customised and comprehensive approach to face the complexity inherent to health systems. Yet, limited knowledge is available on how policies could enhance the performance of the system and how multi-stakeholder efforts could give rise to changes in health policy. We aimed to analyse the ongoing participatory action research and, more specifically, see in how far action research as an embedded research approach could contribute to strengthening health systems. Methods We adopted a single-case study design, based on two subunits of analysis, i.e., two selected districts. Qualitative data were collected by analysing country and programme documents, conducting 12 semi-structured interviews and performing participatory observations. Interviewees were selected based on their current position and participation in the programme. The data analysis was designed to address the objectives of the study, but evolved according to emerging insights and through triangulation and identification of emergent and/or recurrent themes along the process. Results An evaluation of the progress made in the two districts indicates that continuous capacity-building and empowerment efforts through a participative approach have been key elements to enhance dialogue between, and ownership of, the actors at the local health system level. However, the strong hierarchical structure of the Mauritanian health system and its low level of decentralisation constituted substantial barriers to innovation. Other constraints were sociocultural and organisational in nature. Poor work ethics due to a weak environmental support system played an important role. While aiming for an alignment between the flexible iterative approach of action research and the prevailing national linear planning process is quite challenging, effects on policy formulation and implementation were not observed. An adequate time frame, the engagement of proactive leaders, maintenance of a sustained dialogue and a pragmatic, flexible approach could further facilitate the process of change. Conclusion Our study showcases that the action research approach used in Mauritania can usher local and national actors towards change within the health system strengthening programme when certain conditions are met. An inclusive, participatory approach generates dynamics of engagement that can facilitate ownership and strengthen capacity. Continuous evaluation is needed to measure how these processes can further develop and presume a possible effect at policy level.